University athletes' competitive success versus their affective tolerance and stress-tolerance rates - Ismailova, N. I.; Ljdokova, G. M. (Theory and Practice of Physical Culture, 2018)
In the selection process, every coach gives a high priority to the athlete`s personality qualities plus a variety of mental fitness aspects including affective tolerance and stress-tolerance rates. These competitive success factors were rated by the Cattel`s 16 Personality Factor Questionnaire and computerized Activatiometer AC-9K Test System. Objective of the study was to profile the university athletes` personality qualities versus their competitive success rates. Subject to the tests and analyses under the study were personality qualities, affective tolerance and stress-tolerance rates of the 19-21 year-old students (n=60). The study data and analyses showed that the successful university competitors are tested with higher affective tolerance rates; high working capacity maintenance abilities; higher stress-tolerance rates; and high self-control and self-confidence rates. Most of them demonstrate high self-esteem, ambitions and insistence in a variety of competitive situations; versus the unsuccessful university athletes who tend to explain their failures by the process mismanagement factors and misfortunes.